External responsiveness of the Yo-Yo IR Test level 1 in high-level male soccer players - Fanchini, M.; Schena, F.; Castagna, C.; Petruolo, A.; Combi, F.; McCall, A.; Impellizzeri, M. (International Journal of Sports Medicine, 2015)
The aim of this study was to assess the external responsiveness, construct validity and internal responsiveness of the Yo-Yo Intermittent Recovery test level 1 and its sub-maximal version in semi-professional players. Tests and friendly matches were performed during the preseason and regular season. The distance covered above 15 km/h was considered as an indicator of the physical match performance. Construct validity and external responsiveness were examined by correlations between test and physical match performance (preseason and regular season) and training-induced changes. Internal responsiveness was determined as Cohen`s effect size, standardized response mean and signal-to-noise ratio. The physical match performance increased after training (34.8%). The Yo-Yo Intermittent Recovery test level 1 improved after training (40.2%), showed longitudinal (r=0.69) and construct validity (r=0.73 and 0.59, preseason and regular season) and had higher internal responsiveness compared to its sub-maximal version. The heart rate at the 6th minute in the sub-maximal version did not show longitudinal (r=-0.38) and construct validity (r=0.01 and -0.06, preseason and regular season) and did not significantly change after training (-0.3%). The rate of perceived exertion decreased in the sub-maximal version (-?29.8%). In conclusion, the Yo-Yo Intermittent Recovery test level 1 is valid and responsive, while the validity of its sub-maximal version is questionable.